Educação bilíngue de surdos no Município de Fortaleza/CE: avaliação da Meta 1 no Eixo Educação Especial do PME (2015-2025) - Lima, Maria Patrícia Barros (2025)
This research focuses on bilingual education for deaf students, with its main object of study being Goal 1 of the Special Education axis from the Municipal Education Plan (PME) of Fortaleza (Law 10.371/2015). It analyzes the implementation of the operational strategies of Goal 1, concerning the education of deaf students in Fortaleza between 2015 and 2025, highlighting its implications and challenges. The study adopts a qualitative, descriptive, and explanatory approach, conducted in two stages: a bibliographic and documentary review for the theoretical foundation, and field research through the application of questionnaires in two schools of the Municipal Department of Education (SME) of Fortaleza. Data analysis was performed using content analysis methodology, framed within an in-depth evaluation perspective. The theoretical foundation and discussion of analysis categories 4 public policies, social and educational policies, special and inclusive education, with a focus on Libras and deaf students 4 relied on authors such as Choi et al. (2011), Goldfeld (1997), Moura (2005), Quadros and Karnopp (2007), Quadros and Schmiedt (2006), and Perlin (2005). Discussions on bilingual education policies for Brazilian deaf students and the theoretical and methodological conceptions necessary for public policy creation were supported by Araújo (2018), Maia (2015), and Albres and Neves (2013). Results indicate that the PME of Fortaleza (201532025) requires adjustments regarding the operational strategies for deaf students, including teacher training for bilingual education, development of adapted individual assessment tools, provision of bilingual didactic and pedagogical resources, creation of a bilingual curriculum for deaf students, and the mandatory inclusion of Libras as a subject in all regular classrooms. These changes are essential to meet the requirements of laws concerning bilingual education for deaf students and to promote a quality and inclusive educational environment.